Peran Mediasi dalam Menyelesaikan Sengketa Tanah Sebagai Alternatif Penyelesaian Sengketa di Luar Pengadilan: Studi Kasus di Desa Sumberjaya Kecamatan Tempuran Kabupaten Karawang - Andi Muhamad Bintang S; Lia Amaliya; Da’i Safuad Ixal; Muhamad Aldy Ardiansyah; Zulfiansyah Yusuf Suroso (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Agrarian law legally regulates land, with Law Number 5 of 1960 concerning Basic Agrarian Regulations as its juridical basis. Land disputes are one of the land issues that often occur in Indonesia, with complicated and unique problem characteristics, which are different from problems in other fields. An example of a land dispute occurred in Sumberjaya Village. Settlement of land disputes can be done through various means, both through the courts and outside the courts, such as Negotiation, Arbitration, Conciliation, and Mediation. The focus of this article is to gain an understanding of how mediation plays a role in land dispute resolution as an alternative dispute resolution that does not involve the court and how land disputes are resolved in Sumberjaya Village through mediation. This article uses empirical juridical research methods. The results show that mediation plays an important role in the process of resolving land disputes, although there are weaknesses in its application. In an effort to resolve land disputes in Sumberjaya Village, the disputing parties have attempted to settle through mediation dozens of times, but there are obstacles and constraints in the form of difficulties in harmonizing the interests of the parties involved in the conflict, as well as difficulties in ensuring their presence in the mediation process, which causes until now the land dispute in Sumberjaya Village has not yet had a meeting point in its resolution.